(untitled) (Società e diritti, 2017)
European law is the basis for legal changes. Categories of European law concepts and tools contribute to the creation and dissemination of principles, rules and practices that circulate more quickly into national legislation. The author with comparative method provides examples of such developments in the area of public procurement Key words: Legal chance, Europe, judicial interpretation